Is either arterial or venous antithrombin III level linked to outcome in elderly males versus females with severe sepsis? - Adly, Nermien N; Abou-Hashema, Rania M (Asian Journal of Medical Sciences, 2014)
Objectives: We aimed to study arterial and venous ATIII levels, in elderly males and females with severe sepsis, and their impact upon the patients’ outcomes. Patients and Methods: A cohort study was performed in thirty-nine elderly patients with severe sepsis. Arterial and venous ATIII levels were measured. Sequential Organ Failure Assessment (SOFA) score was calculated. Results: Both arterial and venous ATIII levels were negatively correlated with age in the whole sample (P=0.004 and .05 consecutively) (r = −0.45 and −0.32 consecutively). There was a significant difference between the arterial and venous ATIII levels in males (P=0.04). In males, SOFA score was positively correlated with arterial ATIII and the difference between arterial and venous ATIII levels (P=0.04 and .05 consecutively). Arterial and venous ATIII were the significant predictors of SOFA score, only in males (P <0.001 and 0.003 consecutively). Conclusion: ATIII level decreased with increasing age. In males, both higher arterial and lower venous ATIII levels were significant predictors of worse organ dysfunction. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10795 Asian Journal of Medical Sciences Vol.6(1) 2015 34-39